Microtopography of Immune Cells in Osteoporosis and Bone Lesions by Endocrine Disruptors - Toni, Roberto; Di Conza, Giusy; Barbaro, Fulvio; Zini, Nicoletta; Consolini, Elia; Dallatana, Davide; Antoniel, Manuela; Quarantini, Enrico; Quarantini, Marco; Maioli, Sara; Bruni, Celeste Angela; Elviri, Lisa; et al. (Frontiers in Immunology, 2020)
Since its first descriptions between the 18th and 19th centuries and seminal studies at the half of the 20th century by the american endocrinologist Fuller Albright, osteoporosis has been ascribed to an unbalance between bone mineral resorption and deposition. Among the numerous cellular players responsible for this unbalance bone marrow monocytes / macrophages, T and B lymphocytes, and dendritic cells play a role in regulating osteoclasts (OC), osteoblasts (OB), and their progenitor cells through interactions occurring in the three-dimensional (3D) context of different bone compartments (cortical and cancellous). Therefore, we have started to engineer 3D bone organoids based on the so called “organomorphic principle” that implies recapitulation of the 3D anatomy of both bone compartments, to be used as in vitro experimental tools for basic and translational research on osteoporosis. The central idea has been to implement a natural bone scaffold with a biomaterial scaffold mimicking the 3D microarchitecture of the blood vessel network of the native bone, to eventually be functionalized with osteogenic, vasculogenic, and immunogenic factors. Based on the topobiological / tensegrital role of the 3D tissue architecture, we have predicted key mechano-chemical interactions between reconstructed vessels and seeded OB, OC, their progenitors, endothelial, smooth muscle, and immune cells. In this manner, in vitro self-assembly of 3D basic multicellular units could be pursued keeping control of both the geometry of the physical context where the cellular interactions occur and type of interacting cells. As a proof-of-concept of our pre-clinical model, we here present results showing that the 3D geometry of the fibrous and biomaterial-reconstituted vascular components of decellularized and/or decalcified, 3D macroscopic matrices from the adult male rat scapula may efficiently in vitro drive cortical and cancellous homing of mesenchymal stromal cell differentiating to OB, leading to 3D bone organoids with 3D structural features consistent with mineral deposition. In this manner, we provide an innovative in vitro system for eventual study of the remodelling role of bone and immune cells and their response to manipulations of the endocrine, metabolic and inflammatory milieu including interactions with endocrine disrupting chemicals, all known to increase the risk of osteoporosis.